1982
DOI: 10.1523/jneurosci.02-01-00090.1982
|View full text |Cite
|
Sign up to set email alerts
|

Long loop and spinal reflexes in man during preparation for intended directional hand movements

Abstract: Advance information about the direction of a movement to be performed in a reaction time (RT) paradigm is known (I) to improve performance, (2) not to result in any related change in monosynaptic spinal reflexes triggered at the time of the response signal, and (3) to trigger related changes in the activity of a number of neurons in the motor cortex.The aim of this experiment was to compare the evolution of the early (Ml) and late (M2) responses to a muscular overload during the foreperiod of an RT task, accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…According to Student's paired t-test, there was no signi®cant dierence in latency between the non-action and the target-alignment tasks [M1, t À0X07, df 25, not signi®cant (NS); M2, t À0X98, df 25, NS]. The latencies of these re¯ex components are similar to values reported in previous studies that examined the re¯ex activities of forearm muscles (Lee and Tatton 1975;Bonnet and Requin 1982;Abbruzzese et al 1985).…”
Section: Latency Of Each Re¯ex Componentsupporting
confidence: 82%
See 1 more Smart Citation
“…According to Student's paired t-test, there was no signi®cant dierence in latency between the non-action and the target-alignment tasks [M1, t À0X07, df 25, not signi®cant (NS); M2, t À0X98, df 25, NS]. The latencies of these re¯ex components are similar to values reported in previous studies that examined the re¯ex activities of forearm muscles (Lee and Tatton 1975;Bonnet and Requin 1982;Abbruzzese et al 1985).…”
Section: Latency Of Each Re¯ex Componentsupporting
confidence: 82%
“…The gain of these re¯ex activities, particularly the long-latency components, has been reported to be modi®ed by anticipation of a stimulus and by motor preparation for the direction and type of movement (Nashner 1976;Rothwell et al 1980;Hallett et al 1981;Bonnet and Requin 1982;Al-Falahe and Vallbo 1988;Gielen et al 1988;Yamamoto and Ohtsuki 1989;Johnson et al 1991;Doemges and Rack 1992a,b;Goodin and Amino 1992). Furthermore, some studies have reported that the degree of change in long-latency activity was more remarkable for the subjects with short reaction times than for those with long reaction times, and that the long-latency component was modi®ed by motor preparation for the reaction movement (Bonnet 1983;Woollacott et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Another important point to note is that, in both conditions, the change in CS excitability involved the muscle that was stretched when a central perturbation occurred during the NINT trials. In fact, muscle stretch (mechanically induced by a rapid joint angular displacement) is well known to trigger a set of EMG responses composed of short‐ and long‐latency components (Rothwell et al ., 1980; Bonnet & Requin, 1982). Using the same instructions to ‘prepare to resist’ vs. ‘to prepare to let go’ when facing such a rapid joint angular displacement, it was shown several times that the long‐latency stretch response was modulated by the type of instruction (Rothwell et al ., 1980; Bonnet & Requin, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…We know that during preparation inhibition occurs at the segmental spinal level: hence the decrease of spinal reflexes during the preparatory period and their reincrease shortly before the movement starts [6]. The pattern of spinal excitability during motor simulation, with a marked increase in T-reflex, is thus closer to that of real action than that of preparation.…”
Section: Physiological Correlates Of Mental Simulation Of Movementmentioning
confidence: 96%